Law Brakes to Protect Victims of Sexual Violence Against Children and Women in the Private Field - I Made Wahyu Chandra Satriana; Ni Made Liana Dewi (Warmadewa Press, 2022)
Various laws and regulations have been established to prevent sexual violence against children and women. Various violations in the laws and regulations have been made to minimize the occurrence of sexual violence, especially in the private sphere. This private domain is a family area where the perpetrator is a person who is still related by blood, kinship, marriage or who has an intimate relationship with the victim. This is what causes the victim does not dare to report to the authorities. One of them is the case of a 12-year-old child in Medan who became a victim of his mother's girlfriend and ended up suffering from the HIV virus. Based on this, the problem in this study is how to violate the law in protecting victims of violence against children and women in the private sphere. This study aims to find out legal breakthroughs in protecting victims of sexual violence against children and women in the private sphere. This study uses a normative juridical research method, because there is an examination of norms regarding legal protection for victims of violence against children and women in the private sphere. This research uses library law sources. The establishment of Law Number 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT) aims to provide protection to women. Meanwhile, legal protection for children is contained in Law Number 17 of 2016 concerning Stipulation of Government Regulation in Lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection. The law has not been able to prevent and track sexual violence that occurs in the private sphere. The government finally made a breakthrough to form Law No. 12 of 2022 concerning the Crime of Sexual Violence.